THE ISSUE OF THE RECOVERY OF THE ECONOMIC SOVEREIGNTY IN RA - Karyan, Ara (Bulletin of Yerevan University G: Economics, 2019)
The article discloses the problem of restoring economic sovereignty in Armenia. The article notes the need and steps to combat corruption, patronage, and monopolies. The basis of economic sovereignty on the unreasonable transfer of the function of subsidizing beneficiaries of natural gas and electricity to the operators of natural monopolies in these areas is indicated. The format of the solution is based on the introduction of an excise tax on energy carriers – natural gas and electricity. It underlines the failure of the price increase argument and that the proposed solution will ensure a real fight against corruption and restore economic sovereignty, will implement the necessary tax reforms, will ensure a steady growth in budget revenues, and reduce the overwhelming burden of external public debt.